Effects of Early, Small-Scale Nitrogen Addition on Germination and Early Growth of Scots Pine (Pinus sylvestris) Seedlings and on the Recruitment of the Root-Associated Fungal Community - Castro, David; Schneider, Andreas N.; Holmlund, Mattias; Näsholm, Torgny; Street, Nathaniel R.; Hurry, Vaughan (2021)
Scots pine (Pinus sylvestris L.) is one of the most economically important species to the Swedish forest industry, and cost-efficient planting methods are needed to ensure successful reestablishment after harvesting forest stands. While the majority of clear-cuts are replanted with pre-grown seedlings, direct seeding can be a viable option on poorer sites. Organic fertilizer has been shown to improve planted seedling establishment, but the effect on direct seeding is less well known. Therefore, at a scarified (disc trencher harrowed) clear-cut site in northern Sweden, we evaluated the effect of early, small-scale nitrogen addition on establishment and early recruitment of fungi from the disturbed soil community by site-planted Scots pine seeds. Individual seeds were planted using a moisture retaining germination matrix containing 10 mg nitrogen in the form of either arginine phosphate or ammonium nitrate. After one growing season, we collected seedlings and assessed the fungal community of seedling roots and the surrounding soil. Our results demonstrate that early, small-scale N addition increases seedling survival and needle carbon content, that there is rapid recruitment of ectomycorrhizal fungi to the roots and rhizosphere of the young seedlings and that this rapid recruitment was modified but not prevented by N addition.